Statistical Analysis Of 750 Cleft Lip And Palate Patients - Sam D. Theogaraj; Sam D. Theogaraj; L. B. M. Joseph; Mani M. Mani (Indian Journal of Plastic Surgery)
1. 750 cleft lip and palate cases have been analysed.